Crystal structure of 3-(thiazol-2-ylcarbamoyl)-7-oxabicyclo[2.2.1]heptane-2-carboxylic acid, C11H12N2O4S - Song Jinqing; Cui Beibei; Mi Xia; Zhang Jingyu (Zeitschrift für Kristallographie - New Crystal Structures)
C11H12N2O4S1, orthorhombic, Pbca (no. 61), a = 11.08447(14) Å, b = 10.71473(16) Å, c = 19.5463(3) Å, V = 2321.46(6) Å3, Z = 8, R gt(F) = 0.0450, wR ref(F 2) = 0.1275, T = 293(2) K.